Pengaruh Manajemen Sarana Pendidikan terhadap Kepuasan Belajar Siswa di MTs Al-Muawanah Susukanlebak Kecamatan Susukanlebak Kabupaten Cirebon - Dhia Salsabila; Subur SUbur; Ahmad Amin Mubarok (JIEM (Journal of Islamic Education Management), 2022)
ABSTRACTManajement of educational facilities is very important in supporting student learning satisfaction. The educational facilities at MTs Al-Muawanah Susukanlebak, Susukanlebak District, Cirebon Regency are inadequate, but student learning satisfaction is quite high. The aims of this research are (1) Management of educational facilities at MTs Al-Muawanah Susukanlebak, Susukanlebak District, Cirebon Regency.  (2) Student learning satisfaction at MTs Al-Muawanah Susukanlebak, Susukanlebak District, Cirebon Regency. (3) The effect of educational facilities management on student learning satisfaction at MTs Al-Muawanah Susukanlebak, Susukanlebak District, Cirebon Regency.  This study uses a quantitative method with a causal ex-post facto research design. The total population in this study amounted to 296 with a sample of 10% of the total population using the Cluster Random Sampling technique as many as 30 respondents.  Based on the results of analytical research that the management of educational facilities at MTs Al-Muawanah Susukanlebak is included in the good category with a percentage of 71.75%. Meanwhile, student learning satisfaction at MTs Al-Muawanah Susukanlebak is included in the good category with a percentage of 72.28%.  There is a significant effect between Educational Facilities Management (X) on Student Learning Satisfaction (Y), with a significant value of 0.000 <0.05. The amount of influence contributed by the Management of Educational Facilities on Student Learning Satisfaction is 76.9%, the remaining 23.1% is influenced by other variables not examined in this study.  Keywords: Management, Educational Facilities, Student Learning Satisfaction ABSTRAKManajemen sarana pendidikan sangat penting dalam menunjang kepuasan belajar siswa. Sarana pendidikan yang ada di MTs Al-Muawanah Susukanlebak Kecamatan Susukanlebak Kabupaten Cirebon kurang memadai akan tetapi kepuasan belajar siswa cukup tinggi. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh manajemen sarana pendidikan terhadap kepuasan belajar siswa di MTs Al-Muawanah Susukanlebak Kecamatan Susukanlebak Kabupaten Cirebon. Penelitian ini menggunakan metode kuantitatif dengan desain penelitian yaitu Ex-post Facto yang bersifat kausal. Adapun jumlah populasi pada penelitian ini berjumlah 296 dengan pengambilan sampel 10% dari jumlah populasi menggunakan teknik Cluster Random Sampling yaitu sebanyak 30 responden. Berdasarkan hasil penelitian secara analisis bahwa manajemen sarana pendidikan di MTs Al-Muawanah Susukanlebak termasuk dalam kategori baik dengan persentase sebesar 71,75%. Sedangkan kepuasan belajar siswa di MTs Al-Muawanah Susukanlebak termasuk dalam kategori baik dengan persentase sebesar 72,28%. Terdapat pengaruh yang signifikan antara Manajemen Sarana Pendidikan (X) terhadap Kepuasan Belajar Siswa (Y), dengan nilai signifikan 0,000 < 0,05. Besarnya pengaruh yang disumbangkan oleh Manajemen Sarana Pendidikan terhadap Kepuasan Belajar Siswa adalah sebesar 76,9% sisanya sebesar 23,1% dipengaruhi oleh variabel lain yang tidak diteliti dalam penelitian ini. Kata Kunci : Manajemen, Sarana Pendidikan, Kepuasan Belajar Siswa